KELAYAKAN SARANA DAN PRASARANA BENGKEL BUBUT DI SMK BINAKARYA 1 KARANGANYAR - Afri Fajar Mustava; Suparmin; Alfat Khaharsyah (JURNAL VOKASI DEWANTARA (JVD), 2025)
This research aims to: (1) Determine the adequacy of lathe workshop facilities at SMK BinaKarya 1 Karanganyar; (2) Assess the feasibility of lathe workshop infrastructure at SMKBina Karya 1 Karanganyar; and (3) Evaluate the adequacy of facilities and infrastructureas a whole. This research uses quantitative methods. The tools utilized in the researchinclude observation, interviews, notes, and observation sheets with assessment checklistsand assessment scale templates. The data analysis technique employed is quantitativedescriptive analysis. The object of this research is the facilities and infrastructure of a lathemachine workshop, particularly the construction of the machine shop, machine shopfurniture (workbenches, measuring tools, lathes, mills, grinders, instructions, andmaintenance), processing equipment, and teaching media in machine and other equipmentworkshops. These aspects are evaluated based on the standards of facilities andinfrastructure as outlined in the Ministry of Education and Culture Regulation Number 34of 2018 regarding National Education Standards. The results of this research show: (1) Thefeasibility level for building machine factory infrastructure is 94.11% (very feasible); (2)The feasibility of facilities such as tables and chairs, factory equipment, props, and otherequipment is 88.58% (very feasible); and (3) The overall observation results indicate thatthe level of machine shop facilities and infrastructure is 90.07% (very feasible).